Multiphase shear thickening fluid-Kevlar fiber composite material as well as preparation method and application thereof
By integrating CNC or SiC additives into the shear thickening fluid, the STF-Kevlar composite material achieves improved impact resistance and energy absorption, addressing temperature response limitations and enhancing performance in high-impact applications.
Patent Information
- Application Number
- CN202510463632.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2025-07-15
- Estimated Expiration
- 2045-04-14
AI Technical Summary
The existing STF-Kevlar composite materials have insufficient impact resistance under high energy impact, and their response to temperature changes is not systematic enough, and the rheological performance research is not comprehensive enough, which ignores the impact of STF energy absorption and heating.
Add the modified additives CNC or SiC to the shear thickening liquid to prepare a multiphase shear thickening liquid, and immerse Kevlar fibers in the multiphase shear thickening liquid, and evaluate the performance through electron microscopy experiments, rheology experiments and impact tests.
It significantly improves the protective performance of composite materials, enhances the impact resistance of Kevlar fiber cloth, improves temperature applicability and rheology performance, and improves energy absorption efficiency.
Smart Images

Figure CN120311486A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of novel composite materials, and particularly relates to a multiphase shear thickening fluid-Kevlar fiber composite material, a preparation method and an application thereof. Background Art
[0002] The research and application of protective materials have become the key research content in the field of composite material research in the current era of rapid technological development. The research and development of safe and reliable new protective materials and the improvement of the performance of existing protective structures have a profound impact on the safety guarantee issues in many fields. At present, in the fields of industrial safety, sports, especially military protection, there is an urgent need to research and develop protective materials, protective structures and protective equipment with high impact resistance. For practical application scenarios such as explosion and impact, which have the characteristics of high instantaneous load, high energy release and high dynamic response, the protective materials applied to such scenarios need to have good energy absorption characteristics. High-performance fiber fabrics with high strength, high toughness and light weight, such as aramid fibers, ultra-high molecular weight polyethylene fibers (UHMWPE), carbon fibers, glass fibers, etc., are usually used as basic materials for the research and development of soft armor. Among them, the high-performance synthetic Kevlar fiber invented by DuPont in 1965 in aramid fibers is the most widely used. Such soft armor abandons the disadvantages of traditional hard armor, such as being heavy, inconvenient to wear and restricting the movement of the wearer's body parts. It still has excellent energy absorption characteristics and impact resistance under the premise of ensuring flexibility and convenience, and provides protection for the wearer under the threat of energy impact. A large number of studies on high-performance fabric materials show that although pure fabric materials have great potential for anti-impact protection, in order to maximize the resistance to the damage caused by impact energy to the human body, multiple layers of Kevlar fabrics need to be stacked, which also makes the thickness of traditional soft armor relatively high and too heavy in actual use. In order to solve the problem of insufficient performance of pure fabric soft armor on the basis of being light and flexible, it is necessary to enhance the anti-impact performance of a single layer of Kevlar fabric.
[0003] Impregnating high-performance fabrics with shear thickening fluid (STF) has become a potential method and a key research direction for enhancing the impact resistance of single-layer fabrics. As a special concentrated suspension with intelligent response, STF has unique rheological characteristics where the fluid viscosity changes with the shear rate. At low shear rates, its viscosity decreases, showing good fluidity. When the shear rate gradually increases beyond the critical shear rate, its flow viscosity surges, and even exhibits solid-like characteristics at high dispersed-phase mass fractions. When the shear rate continues to increase, STF finally shows shear-thinning rheological characteristics, making the rheological performance curve exhibit an "S-shaped" feature. Regarding the viscosity change characteristics of STF, the current mainstream explanations for its microscopic basic principles are the "order-disorder transition theory", the "particle cluster theory", and the "fluid lubrication-frictional contact theory". Based on the above microscopic thickening principles, according to the viscosity increase rate during its thickening stage, the thickening behavior of STF is divided into continuous shear thickening (CST) and discontinuous shear thickening (DST). In particular, the viscosity increase by several orders of magnitude shown by discontinuous shear thickening will play an important role in reinforcing Kevlar fiber cloth. The use of STF dispersed in ethylene glycol solution to impregnate Kevlar fibers was first proposed by Wagner et al. Ballistic experiments showed that the bulletproof penetration resistance of the composite material was significantly enhanced, and the flexibility of the material was hardly lost. Subsequently, the research on STF-impregnated fiber cloth mainly focused on changing STF, replacing high-performance fiber cloth, and special thin-layer structures. Qin (cpb) et al. changed the STF dispersion medium to ionic liquids (ILs), which transformed the rheological properties of STF from traditional unimodal shear thickening behavior to bi-continuous shear thickening behavior. At the same time, the anti-puncture performance, mechanical properties, and electromagnetic interference shielding ability of the impregnated fabric were significantly enhanced. Sheng (tws) et al. replaced the traditional SiO2 particles in the dispersed phase with polystyrene microspheres to prepare a new type of STKF-impregnated Kevlar fabric. Puncture experiments showed that the tensile strength of this soft composite material increased by more than 55%, and the maximum pull-out force increased by more than 6 times. Pan (cej) et al. used SiO2 / ethanol system STF to impregnate fabrics. In addition to mechanical property tests, the anti-flame-retardant performance of the composite material was mainly studied, and the conclusion was that the STF-Kevlar composite material had excellent anti-flame-retardant performance and still had good toughness and mechanical properties after heat treatment at 400 °C. Xie (md) et al. analyzed the anti-impact mechanism of STF-Kevlar composite materials by means of fluid-structure interaction based on the finite element numerical analysis software LS-DYNA. The results showed that the anti-impact ability of the composite material was much greater than that of pure fabric, and when the impact velocity was relatively high, STF was the main energy-absorbing part.
[0004] Although current research has extensively studied the mechanical properties and electrothermal conductivity of STF-Kevlar composites in many aspects, the STF mainly remains a traditional single-dispersed-phase shear thickening system, and the research on STF modification treatment is not deep enough. In addition, the current research does not comprehensively explore the rheological properties of STF. Some studies on rheology ignore the fact that STF absorbs energy and heats up during impact, and there is no systematic elaboration on the response of STF to temperature changes. Summary of the Invention
[0005] In view of the above problems, the present invention aims to provide a multiphase shear thickening fluid-Kevlar fiber composite material, its preparation method and application. The composite material is prepared by adding a modified additive CNC or SiC to the shear thickening fluid to prepare a multiphase shear thickening fluid, and then impregnating Kevlar fibers in the multiphase shear thickening fluid. The multiphase shear thickening fluid can significantly enhance the ability of Kevlar fiber cloth to resist impact deformation and absorb impact energy.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A preparation method of a multiphase shear thickening fluid-Kevlar fiber composite material, comprising the following steps:
[0008] S1: Add a modified additive to the shear thickening fluid to prepare a multiphase shear thickening fluid;
[0009] S2: Use the multiphase shear thickening fluid prepared in step S1 to impregnate Kevlar fibers to obtain a multiphase shear thickening fluid-Kevlar fiber composite material
[0010] Further, the modified additive described in step S1 includes CNC or SiC.
[0011] Further, the specific operation of step S1 includes the following steps:
[0012] S101: Gradually add nano-SiO2 to the dispersion medium PEG200 and stir until it becomes a homogeneous suspension to obtain a shear thickening fluid without a reinforcing phase;
[0013] S102: Gradually add the modified additive CNC or SiC to the shear thickening fluid and stir evenly to obtain a multiphase shear thickening fluid sample containing a reinforcing phase;
[0014] S103: Cure the multiphase shear thickening fluid sample at a constant temperature and humidity for 12 hours to remove the bubbles in the sample and obtain a finished multiphase shear thickening fluid.
[0015] Further, the mass ratio of nano-SiO2 to PEG200 is 5 - 7:3 - 5; the mass ratio of nano-SiO2 to the modified additive is 5 - 7:1 - 3.
[0016] Further, the conditions for constant temperature and humidity curing in step S103 are: 30°C and 95% humidity.
[0017] Further, the specific operations of step S2 include the following steps
[0018] S201: Dilute the multiphase shear thickening fluid prepared in step S1 with absolute ethanol, and ultrasonically disperse and mix evenly;
[0019] S202: Immerse the Kevlar fiber cloth in the mixed solution of step S201 and stir, then take it out and dry it to obtain the multiphase shear thickening fluid - Kevlar fiber composite material.
[0020] Further, in step S202, the impregnation time of the Kevlar fiber cloth is 5 min, the drying temperature is 40°C, and the drying time is 6 h.
[0021] In addition, the present invention also provides a multiphase shear thickening fluid - Kevlar fiber composite material prepared by the preparation method as described above.
[0022] In addition, the present invention also provides the application of the multiphase shear thickening fluid - Kevlar fiber composite material as described above in anti-impact protection materials.
[0023] In addition, the present invention also provides a performance testing method for the multiphase shear thickening fluid - Kevlar fiber composite material as described above, including the following steps
[0024] Step a: Conduct an electron microscopy experiment on the multiphase shear thickening fluid - Kevlar fiber composite material;
[0025] Step b: Conduct room temperature rheology experiments and variable temperature rheology experiments on the multiphase shear thickening fluid;
[0026] Step c: Conduct a single yarn quasi-static tensile mechanical test on the multiphase shear thickening fluid - Kevlar fiber composite material;
[0027] Step d: Conduct a pull-out test on the multiphase shear thickening fluid - Kevlar fiber composite material under impact load;
[0028] Step e: Conduct a drop hammer impact test on the multiphase shear thickening fluid - Kevlar fiber composite material. The beneficial effects of the present invention are:
[0029] 1. The present invention innovatively adds CNC and SiC modified additives to the shear thickening fluid to modify STF, impregnates Kevlar high-performance fiber cloth in MSTF to prepare a composite material, and conducts performance tests on the prepared multiphase shear thickening fluid-Kevlar fiber composite material through electron microscopy experiments, room temperature rheology, variable temperature rheology, single yarn quasi-static tension, yarn pull-out, drop hammer impact experiments, etc. The results show that the addition of CNC and SiC can significantly improve the protective performance of the composite material, which provides a theoretical support and experimental basis for the development of high-performance protective soft armor of MSTF-Kevlar fiber composite material in the field of impact protection.
[0030] 2. In the present invention, Kevlar fibers are impregnated in the modified MSTF. Due to the good microscopic morphology of the modified MSTF, the modified additives have an obvious modification effect on the agglomeration of MSTF particles, enabling MSTF to be evenly dispersed on the surface of Kevlar fibers, and the adhesion degree and adhesion structure are both ideal; moreover, it can change the form of particle clusters and increase the particle stiffness. Under variable temperature conditions, the modified additives can effectively increase the temperature range of the shear thickening interval, enhancing the temperature applicability of the MSTF system.
[0031] 3. The multiphase shear thickening fluid-Kevlar fiber composite material prepared in the present invention shows a significant upward trend in force. At the same time, the ultimate load of the MSTF-Kevlar composite material in the elastic stage is also significantly greater than that of the pure Kevlar fiber cloth. The shear thickening effect increases the energy absorption values in the elastic stage and the oscillation stage, making the impact energy absorption effect of the MSTF-Kevlar composite material significant. Brief Description of the Drawings
[0032] Figure 1 It is the preparation flow chart of the multiphase shear thickening fluid-Kevlar fiber composite material in the present invention, and the corresponding performance test diagrams; among them, (a) is the preparation flow chart of the multiphase shear thickening fluid-Kevlar fiber composite material; (b) is the microscopic schematic diagram of the MSTF-Kevlar fiber composite material; (c) is the rheology experiment diagram; (d) is the single yarn quasi-static fracture and yarn pull-out experiment diagram; (e) is the drop hammer impact test diagram.
[0033] Figure 2 It is the electron microscopy diagrams of nano-SiO2, CNC, and SiC in the present invention.
[0034] Figure 3 It is the electron microscopy diagrams of four types of MSTF (STF) prepared with 30wt% SiO2, 68wt% SiO2, 65wt% SiO2 + 3% CNC, and 65wt% SiO2 + 3% SiC in the present invention.
[0035] Figure 4Electron micrographs of STF-Kevlar fiber composites prepared from pure Kevlar fiber cloth, MSTF (STF) corresponding to 60 wt% SiO2, 57 wt% SiO2 + 3% CNC, and 57 wt% SiO2 + 3% SiC in the present invention.
[0036] Figure 5 Rheological experiment results of MSTF (STF) with ratios of 30 wt% SiO2, 28.5 wt% SiO2 + 1.5 wt% CNC, and 28.5 wt% SiO2 + 1.5 wt% SiC in the present invention.
[0037] Figure 6 Rheological property experiment results of MSTF with a fixed mass fraction of 60 wt% total dispersed phase (SiO2 and modified additives) in the present invention.
[0038] Figure 7 Rheological property experiment results of MSTF at room temperature with different mass fractions of modified additives when the mass fraction of SiO2 dispersed phase is fixed at 65 wt% and 68 wt% in the present invention.
[0039] Figure 8 Variable-temperature rheological experiment results in the present invention.
[0040] Figure 9 Quasi-static tensile mechanical experiment process and results of single yarn in the present invention.
[0041] Figure 10 Experimental photos of single yarn tensile of four groups of MSTF (STF)-Kevlar composites in the present invention.
[0042] Figure 11 Yarn pull-out experiment process and results in MSTF-Kevlar composites in the present invention.
[0043] Figure 12 Experimental pictures of yarn pull-out of four groups of MSTF (STF)-Kevlar composites in the present invention.
[0044] Figure 13 Force-displacement curves of fiber cloth in three drop hammer impact experiments in the present invention.
[0045] Figure 14 Absorbed energy-displacement curves of the first repeated drop hammer impact experiment of MSTF-impregnated Kevlar fiber cloth and pure Kevlar fiber cloth in the present invention.
[0046] Figure 15 Absorbed energy-displacement curves of the second repeated drop hammer impact experiment of MSTF-impregnated Kevlar fiber cloth and pure Kevlar fiber cloth in the present invention.
[0047] Figure 16 This is the energy absorption - displacement curve of the repeated drop - weight impact experiment of the third - time MSTF - impregnated Kevlar fiber cloth and pure Kevlar fiber cloth in the present invention. Detailed implementation manners
[0048] In order to enable those of ordinary skill in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0049] Embodiment 1:
[0050] Embodiment 1 provides a preparation method of a multiphase shear - thickening fluid - Kevlar fiber composite material. The preparation process is as shown in (a) of the attached Figure 1 figure, and includes the following steps:
[0051] S1: Prepare a multiphase shear - thickening fluid using a modified additive CNC or SiC;
[0052] Add nano - SiO₂ spherical particles (particle diameter 300 - 400 nm, spherical particle content more than 60%) into the dispersion medium polyethylene glycol solution (PEG200) in small amounts and multiple times, and use a planetary ball mill to stir until a uniform suspension state is obtained, so as to obtain a shear - thickening fluid (STF) without a reinforcing phase.
[0053] Add the modified additive into the STF multiple times, and perform mechanical stirring again until it is uniformly mixed to obtain a multiphase shear - thickening fluid (MSTF) sample containing a reinforcing phase; the modified additive uses nano - cellulose CNC (nano - diameter 5 - 10 nm) or nano - silicon carbide SiC (particle diameter 20 - 30 nm).
[0054] Put the prepared MSTF sample into a plastic freezing tube for sealing, and place it in a constant - temperature and constant - humidity curing box (30 °C, 95% humidity) for curing for 12 hours to remove the air bubbles in the sample, so as to obtain the finished MSTF.
[0055] Specifically, the mass ratio of nano - SiO₂ to polyethylene glycol (the mass of polyethylene glycol in the polyethylene glycol solution)
[0056] In order to compare the modification effects of different CNCs and SiCs, in this embodiment, a variety of finished MSTFs with different mass fractions of CNCs and SiCs are prepared. The specific material ratio results are shown in Table 1 below.
[0057] Table 1 Material ratio parameters of different finished MSTFs (STFs)
[0058]
[0059]
[0060] Further, step S2: using the finished MSTF prepared in step S1 to impregnate Kevlar fiber to obtain a multiphase shear thickening fluid-Kevlar fiber composite material.
[0061] Specifically, the present invention adopts the method of "dilution-impregnation-drying" to prepare a multiphase shear thickening liquid-Kevlar fiber composite material. Pure Kevlar fiber is selected from 400D plain 100g fiber cloth (thickness 0.17mm) of Lott Carbon Fiber Company; considering that the ethanol solvent has the characteristics of good volatility, low toxicity, economy and safety, the prepared finished MSTF is diluted with anhydrous ethanol, and the mixed liquid is treated with ultrasonic dispersion for 30 minutes to ensure that the finished MSTF and anhydrous ethanol are evenly mixed; then the Kevlar fiber cloth is cut into squares and immersed in the mixed liquid and fully stirred. After immersion for 5 minutes, the impregnated fabric is taken out and placed in an oven at 40°C for 6 hours to obtain a MSTF-Kevlar fiber composite material, which is sealed in a sealed bag.
[0062] For comparison, in this embodiment, finished MSTF (STF) prepared by 60wt% SiO2, 57wt% SiO2+3% CNC and 57wt% SiO2+3% SiC were used to impregnate Kevlar fiber.
[0063] The microscopic diagram of the MSTF-Kevlar fiber composite material prepared in this embodiment is shown in the attached figure. Figure 1 As shown in (b), from the attached Figure 1 As can be seen from (b), the dilution and impregnation method makes the MSTF more evenly covered on the surface of the fiber cloth, and the ethanol solvent will not be introduced into the composite material. The hydrogen bonds mainly exist between the hydroxyl groups on the surface of the shear thickening liquid particles and the dispersion medium, and almost no chemical bonds are produced with the diluent.
[0064] Embodiment 2:
[0065] Example 2 Electron microscopy experiments were performed on the raw materials of nano-SiO2, CNC, SiC and the corresponding MSTF (STF) and MSTF (STF)-Kevlar in Example 1.
[0066] The microstructure of SiO2 powder, two kinds of modified additives (CNC, SiC), and MSTF (STF) with mass fractions of 30wt% SiO2, 68wt% SiO2, 65wt% SiO2 + 3% CNC, and 65wt% SiO2 + 3% SiC was characterized by scanning electron microscopy SEM (ZEISS SIGMA 300). The magnification of 2μm - 200nm was used to observe the microstructure of the raw materials and the morphology of MSTF particle clusters. At the same time, the magnification of 10μm - 500nm of the scanning electron microscope was used to observe the microstructure of three types of MSTF (STF)-Kevlar fiber composites prepared in Example 1, with a focus on the interfacial contact form between MSTF cluster particles and Kevlar fibers, so as to provide a microscopic theoretical basis for explaining the specific role in the impact resistance process of MSTF-Kevlar composites.
[0067] The microscopic characterization results of nano-SiO2, CNC, and SiC are shown in the appendix Figure 2 as follows. Among them, (a) is the microscopic characterization result of SiO2, (b) is the microscopic characterization result of SiC, and (c) is the microscopic characterization result of CNC. From (a) in the appendix Figure 2 it can be seen that the raw material of nano-SiO2 particles has good dispersibility. The particles are spherical in shape with a regular combination of a large silicon atom sphere and two small oxygen atom spheres. The particle size is between 200 - 250nm. The particle morphology is relatively regular and smooth, and they are aggregated in a stacked manner. Their stacking is not dense, there are large voids between particles and no bonding substances, and there is no cluster structure. This indicates that before being configured into a shear thickening fluid, the chemical bond action and agglomeration between particles are not obvious. From (b) in the appendix Figure 2 it can be seen that the morphology of nano-SiC particles is irregular sheet-like and the surface is rough. Due to its irregular and rough surface morphology, the stacking between pure SiC particles can form a mechanically interlocking structure, and there is a certain structural framework between the groups formed by its stacking to resist deformation. Such an appearance structure also provides a physical attachment structure for SiO2 particle clusters around SiC particles in the multiphase shear thickening fluid containing modified additives. At the same time, it can be seen from the magnification of 200nm that there are small irregular fine dust particles between the SiC block particles, and these dust substances fill the voids between the stacked structures formed by the SiC block particles, making the structure more dense. From (c) in the appendix Figure 2It can be seen from (c) that the nanocellulose CNC is generally in the shape of fibrous rods, with a rough surface and cracks on some surfaces. By observing the SEM photos at a higher magnification, it can be seen that its interior is also composed of interconnected fibrous filamentous structures, with good integrity. Due to the special nature of its filamentous arrangement, the nanocellulose structure exhibits anisotropy, a large specific surface area, and high crystallinity. This enables CNC to act as a modified additive in STF to form a "bridge" effect, winding and linking multiple groups of SiO2 clusters to form larger cluster structures, thereby changing the rheological properties of the shear thickening fluid.
[0068] Furthermore, the microscopic characterization results of four types of MSTF (STF) prepared with 30wt% SiO2, 68wt% SiO2, 65wt% SiO2 + 3% CNC, and 65wt% SiO2 + 3% SiC are as shown in the appendix Figure 3 as follows. It can be seen from the appendix Figure 3 that for the STF prepared with 30wt% SiO2, due to its low mass fraction, the dispersed phase SiO2 particles are dispersed in the dispersant, and the particle surfaces are wrapped by the dispersant PEG200. A small number of particles are flocculated, but the dispersion distance between the flocs is large, and the overall state is floating and free, with no obvious agglomeration phenomenon. At the same time, there are a large number of unflocculated and free SiO2 particles. Comparing with the STF prepared with 68wt% SiO2, as the mass fraction of the dispersed phase SiO2 particles increases, the particles are densely arranged and in contact with each other, forming particle clusters, and multiple clusters are connected or close to each other. Such a cluster structure plays a role in the process of shear thickening. When the shear rate increases, the number of clusters increases and a blocking phenomenon occurs, causing the viscosity of the STF to rise sharply.
[0069] The addition of the modified additives CNC and SiC will affect the structure of the SiO2 cluster particles at a high mass fraction. For the MSTF with added CNC, the thickness of the wrapped dispersant is thinner, forming a denser particle cluster structure. For the MSTF with added SiC, the dispersed phase SiO2 particles are more completely wrapped by the dispersant, and the agglomeration phenomenon of the SiO2 particles is obvious, with a certain degree of interparticle cross-linking phenomenon. The SiC particles also form a filling effect in the MSTF. At a higher shear rate, the SiC particles may change the adhesion at the particle interface, promote the aggregation of the particles, and change the shear thickening effect.
[0070] Furthermore, electron microscopy observations were carried out on the three types of MSTF (STF)-Kevlar fiber composites and pure Kevlar fiber prepared in Example 1, and the results are as shown in the appendix Figure 4As shown in the figure, where (a) is the microscopic morphology of pure Kevlar fiber cloth; (b) is the microscopic morphology of STF-Kevlar fiber composite prepared by STF with 60wt% SiO2; (c) is the microscopic morphology of MSTF-Kevlar fiber composite prepared by MSTF with 57wt% SiO2 + 3% CNC; (d) is the microscopic morphology of MSTF-Kevlar fiber composite prepared by MSTF with 57wt% SiO2 + 3% SiC. From the appendix Figure 4 It can be seen that the surface of pure Kevlar fiber filaments is smooth, and there is a large gap between the fibers, with only a small amount of dust between them. After the Kevlar fibers are impregnated with 60wt% SiO2, a large number of silica particles adhere to the surface of the fiber filaments. However, this adhesion is uneven, and there is still a large area of the fiber filament surface that is not adhered, and the adhered area is only a single layer of SiO2 particle adhesion, without forming multi-layer particle adhesion and cluster particles. When two types of additives, CNC and SiC, are added, the particle adhesion rate is significantly improved, and the surface of the fiber filaments is almost completely covered by MSTF particles, and the particle adhesion rate of the CNC additive is greater than that of the SiC additive. The introduction of these two types of modified additives makes the adhered SiO2 show significant cluster structures and layered structures, and the gap between the fibers is significantly reduced, indicating that the multi-phase shear thickening fluid containing modified additives has been successfully introduced into Kevlar fibers, and both the adhesion degree and the adhesion structure are relatively ideal.
[0071] Example 3:
[0072] In Example 3, rheological experiments were carried out on MSTF (STF) with different ratios in Example 1 using a rheometer (Anton Paar MCR302), as shown in (c) of the appendix Figure 1 shown. This rheometer is a rotational rheometer, consisting of a substrate and a rotor. The torque frequency is measured by a sensor at the circumference and further converted into viscosity, so as to obtain the rheological curve of shear rate - viscosity, and the viscosity change behavior of MSTF (STF) at low mass fractions is studied through the rheological curve.
[0073] 1. Rheological experiment of MSTF (STF) at room temperature
[0074] Under the condition of room temperature (30°C), rheological experiments were carried out on MSTF (STF) with the ratios of 30wt% SiO2, 28.5wt% SiO2 + 1.5wt% CNC, and 28.5wt% SiO2 + 1.5wt% SiC. The results are shown in the appendix Figure 5 shown, where (a) is the rheological characteristic curves of the three types of MSTF (STF); (b) is the shear rate - shear stress curves of the three types of MSTF (STF). From the appendix Figure 5It can be seen that under the condition of low mass fraction ratio, the shear thickening process of MSTF is not obvious. Instead, it shows obvious shear thinning phenomenon. When the shear rate is 200 -1 it shows the characteristic of stable viscosity, and both the maximum and minimum viscosities are relatively small. This is because the content of the dispersed phase SiO2 is too small. After the initial structure is destroyed under the shear action, the particles cannot form a cluster structure, resulting in almost no thickening effect after the shear rate reaches 500 -1 The shear stress shows a relatively low value and the total absorbed energy is low, which proves that MSTF with a lower mass fraction does not have good impact resistance.
[0075] Furthermore, the present invention also uses MSTF with a fixed mass fraction of 60 wt% of the total dispersed phase (SiO2 and modified additive) to conduct a room temperature rheological experiment. Specifically, 57 wt% SiO2 + 3 wt% CNC, 57 wt% SiO2 + 3 wt% SiC, 58 wt% SiO2 + 2 wt% CNC, 58 wt% SiO2 + 2 wt% SiC, 59 wt% SiO2 + 1 wt% CNC, and 59 wt% SiO2 + 1 wt% SiC are used for the rheological experiment. The results are as shown in the appendix Figure 6 As shown, where (a) is the rheological characteristic curve and (b) is the shear rate - shear stress curve. From the appendix Figure 6 it can be seen that in the low strain rate range, all MSTFs show obvious shear thinning behavior. The addition of high mass fraction modified additives (3 wt% CNC, 3 wt% SiC) has a certain inhibitory effect on the adverse behavior of shear thinning. After exceeding the critical shear rate, all MSTFs enter the shear thickening range (10 - 100 -1 ), and the viscosities of each ratio of MSTF increase significantly. The MSTF system with 3 wt% CNC shows the highest shear viscosity peak, indicating that the high mass fraction CNC additive effectively enhances the shear thickening effect. The MSTF system with 1 wt% SiC shows the lowest shear viscosity peak, indicating that the SiC additive has limited improvement on the shear thickening effect at a lower mass fraction. Comparing the two ratios of MSTF of 58 wt% SiO2 + 2 wt% CNC and 57 wt% SiO2 + 3 wt% SiC, the curve trends in the shear thinning region are basically similar, but in the shear thickening region, the MSTF system with 2 wt% CNC has a stronger shear thickening effect and a higher shear viscosity peak than the MSTF system with 3 wt% SiC, which indicates that the CNC additive has a stronger shear thickening effect on MSTF than the SiC additive.
[0076] From the perspective of shear stress (appendix Figure 6In (b) of , the initial stress of MSTF with 3 wt% CNC added is higher than that of other ratios, and the peak shear stress is also higher, indicating that the addition of CNC effectively enhances the interaction force between MSTF particles. While for the MSTF system with SiC additive added (such as 3 wt% CNC), the shear stress curve is smoother, indicating that SiC particles are relatively rigid and prone to slip during the shear thickening process. The shear thickening index ηs reflects the shear thickening ability of the MSTF system. The ηs of MSTF with 57 wt% SiO2 + 3 wt% CNC is the largest, reaching 2.96. Therefore, this ratio system has the optimal shear thickening performance.
[0077] Furthermore, in the present invention, with the mass fraction of SiO2 dispersed phase fixed at 65 wt% and 68 wt%, 1 wt% - 3 wt% of CNC and SiC modification additives are added to analyze the influence of different mass fractions of modification additives on the room temperature rheological properties of MSTF under the condition of a fixed mass fraction of SiO2 dispersed phase. The results of the rheological experiment are as follows Figure 7 shown, where (a) is the rheological characteristic curve of 65 wt% + CNC and 65 wt% + SiC; (b) is the shear rate - shear stress curve of 65 wt% + CNC and 65 wt% + SiC; (c) is the rheological characteristic curve of 68 wt% + CNC and 68 wt% + SiC; (d) is the shear rate - shear stress curve of 68 wt% + CNC and 68 wt% + SiC. It can be seen from the following Figure 7 that under the same SiO2 mass fraction, the peak viscosity and the thickening amplitude in the shear thickening interval of MSTF with CNC added are both greater than those of MSTF with SiC added. This indicates that the "bridging" effect generated by the fiber structure of CNC has a greater promotion effect on the shear thickening effect than the SiC additive. Therefore, the energy absorption ability of MSTF containing CNC is more prominent. By comparing the rheological curves of the same additive with different SiO2 mass fractions, it can be seen that the initial viscosity, thickening critical viscosity, peak viscosity, and shear thickening amplitude of MSTF with 68 wt% SiO2 are much greater than those with 65 wt% SiO2. In contrast, the MSTF curves with different additive contents under the same SiO2 mass fraction are relatively close, and the changes in peak viscosity, critical shear rate, and shear thickening amplitude are small. This shows that in the modified MSTF containing additives, the influence of the additive on the shear thickening effect is relatively limited, and the rheological properties are more determined by the mass fraction of the dispersed phase SiO2. The additive is more used to improve some rheological properties of MSTF under a fixed dispersed phase content.
[0078] 2. MSTF (STF) variable temperature rheological experiment
[0079] To study the effect of temperature conditions on the rheological properties of MSTF, this experiment also designed MSTF with the following ratios: 65wt% SiO2 + 3wt% CNC, 66wt% SiO2 + 2wt% CNC, 67wt% SiO2 + 1wt% CNC, 65wt% SiO2 + 3wt% SiC, 66wt% SiO2 + 2wt% SiC, and 67wt% SiO2 + 1wt% SiC. And STF with 68wt% SiO2 was configured as a control group for variable-temperature rheological experiments. A fixed shear rate of 100 s -1 (This shear rate refers to the experimental data under normal-temperature rheology. At a shear rate of 100 s -1 , the shear thickening effect of STF is relatively obvious). With the shear environment temperature as the independent variable and the temperature range of 0 - 120 °C, the results of the variable-temperature rheological experiments are as shown in the appendix Figure 8 . Among them, (a) is the temperature-viscosity curve of each ratio of MSTF; (b) is the temperature / viscosity characteristic curve of each ratio of MSTF.
[0080] From the appendix Figure 8It can be seen that the shear viscosities of all formulations show a three-stage change trend with the increase in temperature. At lower temperatures, the viscosity of MSTF is almost zero. This is because at low temperatures, the intermolecular forces and molecular thermal motion between the dispersion medium PEG200 and the dispersed phase particles are severely inhibited by the low temperature, resulting in a low viscosity in the initial stage of the MSTF variable-temperature rheological curve. When the temperature exceeds the lower critical temperature (about 10 °C - 20 °C), the Brownian motion of the particles increases, and the interaction forces between the dispersed phase particles (such as van der Waals forces and electrostatic interactions) and the fluidity of the base liquid reach equilibrium, and the particles can form strong mutual aggregation, resulting in an obvious shear thickening effect in the system. When the ambient temperature exceeds the upper critical temperature (about 40 °C - 65 °C) and enters the high-temperature region, the molecular thermal motion significantly intensifies, the interfacial interaction between particles weakens, and the particle cluster structure generated during shear thickening is destroyed, causing the viscosity of MSTF to rapidly decrease and the fluidity of the system to increase. By comparing MSTF containing CNC / SiC additives with STF of 68wt% SiO2, it can be seen that both the upper and lower critical temperatures (especially the upper critical temperature) have increased, and the shear thickening temperature range of MSTF containing CNC is slightly larger than that of MSTF containing SiC. This indicates that the additives can effectively increase the temperature range of the shear thickening interval, enhance the temperature applicability of the MSTF system, and ensure that the MSTF system still has good shear thickening energy absorption protection characteristics when applied to protective materials to absorb kinetic energy as internal energy, and avoid the failure of the shear thickening fluid due to temperature changes caused by internal energy absorption. At the same time, it can be noted that under variable-temperature conditions, the peak viscosities of MSTF containing additives are all greater than those of STF of 68wt% SiO2. This indicates that the conclusion that the addition of CNC and SiC additives can effectively increase the shear thickening peak viscosity of the MSTF system still applies under variable-temperature conditions, and the addition of CNC slows down the trend of viscosity decrease of MSTF under high-temperature conditions, making MSTF still have good stability under high-temperature conditions.
[0081] Example 4:
[0082] In Example 4, the force change characteristics of a single yarn of the MSTF-Kevlar composite material prepared in Example 1 under impact and the effects of two types of modified additives (CNC, SiC) on the tensile mechanical responses of a single yarn and internal fibers were studied. In this invention, a universal material testing machine (Instron 5982, force measurement range 0 - 100 kN, measurement accuracy ±0.5% of the indicated value) was used to conduct a quasi-static tensile mechanical experiment on the tensile strength of a single yarn, as shown in the appendix Figure 1As shown in Fig. (d). A single yarn is taken from three types of square MSTF (STF)-Kevlar composites (STF-Kevlar composite obtained by impregnating Kevlar fibers with 60 wt% SiO2, MSTF-Kevlar composite obtained by impregnating Kevlar fibers with 57 wt% SiO2 + 3 wt% CNC, MSTF-Kevlar composite obtained by impregnating Kevlar fibers with 57 wt% SiO2 + 3 wt% SiC), and a pure Kevlar fiber cloth yarn is set as a control. After a single yarn is wound two turns around two pairs of 5 mm × 5 mm square aluminum plates, it is fixed to the loading head of the material testing machine without lateral prestress. The fixed loading rate of the material testing machine is set to 0.5 mm / min, the loading temperature is room temperature, the force and displacement of the loading head are recorded during the loading process, and each group of specimens is repeated four times, as shown in the appendix Figure 9 As shown in Fig. (a) of the appendix, the experimental results are shown in the appendix Figure 9 As shown in Fig. (b) of the appendix.
[0083] From the appendix Figure 9 As can be seen from Fig. (b) of the appendix, in the initial stage, the dispersed phase and dispersed medium of MSTF are attached and filled between fibers. When the loading rate of the material testing machine is low, the shear rate between yarns also responds less. At this time, MSTF exhibits the characteristic of shear thinning, the viscosity decreases, and the fluidity of the system increases. Shear thinning reduces the friction between fibers and at the same time avoids the generation of mechanical coupling between STF and fibers, which has a negative impact on the tensile properties of a single yarn. When the loading rate of the material testing machine is high, MSTF shows shear thickening, the dispersed phase particles form a cluster structure, and a direct mechanical coupling is formed with the yarn. The fluidity of MSTF is greatly reduced, the friction between fibers increases, the tensile load borne by the fibers decreases, and the tensile properties of the yarn increase.
[0084] The stress-strain curves of the four repeated experiments are shown in Fig. (c) of the appendix. Figure 9 As can be seen from Fig. (c) of the appendix Figure 9 As can be seen from Fig. (c) of the appendix, the basic trends of the tensile stress-strain curves of the four groups of materials are the same, mainly divided into the elastic stage where the stress rises with the strain. In this stage, the fiber bundles of the yarns in the elastic region maintain good mechanical properties. After passing the peak stress, the tensile stress of the four groups of materials rapidly drops to zero irregularly. In this stage, the structure of the fiber filaments of the yarns intertwined with each other has been completely destroyed and lost the ability to bear stress, which can be called the failure stage. There is a gentle transition section between the two stages as the yield stage, and the stress reaches the peak in the yield stage.
[0085] The present invention compares the elastic modulus of four groups of materials in four experiments. The elastic moduli of the four groups of materials are shown in Table 2 below. It can be seen from Table 2 that at the low tensile loading rate in this experiment, the modulus improvement of MSTF on single yarn tension is small, and the mechanical properties of the fiber itself play a dominant role. Even for 57wt% SiO2 + 3wt% CNC and 57wt% SiO2 + 3wt% SiC, there is a weakening effect. However, this also indicates that MSTF plays an important role in the tensile properties of the yarn. It can be predicted that at high shear rates, this effect will significantly improve the tensile properties of the yarn. From the trend of the stress-strain curves of the four groups of materials, the yield strains of the three groups of materials after modification treatment are all smaller than that of the pure Kevlar fiber cloth. The yield strain of the yarn of the pure Kevlar fiber cloth can reach more than 4%, and the yield strain of the one with SiC added is the lowest, averaging about 2.5%. This is because SiC particles are embedded between the fiber filaments, and their rough surface will cause mechanical wear on the fiber during the stretching process, thus causing the yarn to enter the failure stage in advance. The general decrease in the yield strain reflects to a certain extent that the MSTF particles reduce the ductility and toughness of the yarn, which is the defect of the modified MSTF-impregnated Kevlar fiber cloth composite material.
[0086] Experimental photos of single yarn tension of four groups of materials are as Figure 10 shown. It can be seen from the Figure 10 appendix that the fracture phenomenon of a single pure Kevlar fiber is obvious, and the fiber at the yarn fracture is brittle fractured. At the fracture of a single yarn impregnated with MSTF, there is an obvious tension resistance phenomenon. The fracture of the modified MSTF yarn with CNC added is relatively neat, and the fracture point position is stable, and the sample shows a more uniform tensile behavior. While the modified MSTF yarn with SiC added shows a smaller deformation, which indicates that the rigid enhancement effect of SiC is significant.
[0087] Table 2 Comparison results of elastic moduli of four groups of materials
[0088]
[0089] Example Five:
[0090] To study the pull-out behavior of yarns and the partial yarn slippage phenomenon in the MSTF-Kevlar composite material under impact loads, in this study, a universal material testing machine (Instron 5982, force measurement range 0 - 100 kN, measurement accuracy ±0.5% of the indicated value) was used to conduct a pull-out experiment on the yarns in the MSTF-Kevlar composite material fiber cloth to evaluate the pull-out behavior of the yarns in the composite material when subjected to impact, as shown in the Figure 1As shown in (d). The pull-out test used three types of regular rectangular fiber cloths with dimensions of 10 cm × 40 cm (Kevlar fiber cloth impregnated with 60 wt% SiO2, Kevlar fiber cloth impregnated with 57 wt% SiO2 + 3 wt% CNC, Kevlar fiber cloth impregnated with 57 wt% SiO2 + 3 wt% SiC), and the pure Kevlar fiber cloth was set as the control group. The warp of the composite fiber fabric was parallel to the long side of the rectangle, and the weft was parallel to the short side of the rectangle to ensure that there was no excessive stress concentration in each part when the material was clamped on the universal testing machine. Since there was no yarn weaving constraint on the long and short sides of the rectangle, the edge yarns were curled by heating with a flame to minimize the loosening of the edge yarns. At the midpoint of one short side, adjacent warp yarns parallel to the long side were taken, wound around a square aluminum plate, and then fixed to the loading head of the universal testing machine. A depression was made at the corresponding position on the other short side so that this part of the depression was not fixed during clamping, and the remaining protruding parts were clamped and fixed by the loading head of the testing machine, so as to produce a pull-out effect on the five yarns fixed on one side during the loading process of the material testing machine. The fixed loading rate of the material testing machine was set at 5 mm / min, the loading temperature was room temperature, and the force and displacement of the loading head were recorded during the loading process. Each group of specimens was repeated three times.
[0091] The specific operation process and experimental results of the pull-out test are shown in the appendix Figure 11 as follows. Among them, (a) is a photo of the pull-out test; (b) is the pull-out test method; (c) is the pull-out force-displacement curve of the pull-out test. The pull-out test was carried out on five yarns. The yarn to be pulled out was drawn out from the middle of the sample and fixed to the upper loading head, and the two sides of the fiber cloth except the yarn to be pulled out on the other side were respectively clamped on the lower loading head. The loading rate was 5 mm / min, and this loading rate corresponded to the lower shear rate of the shear thickening fluid rheological experiment, as shown in (a) of the appendix Figure 11 shown. In this yarn pull-out test, the elastic characteristics of the yarn itself, the structural characteristics of the plain weave of the fiber cloth, and the STF filled between the yarns will have a major impact on the macroscopic pull-out behavior of the yarn. As Figure 11As shown in (b) therein, at the initial stage of the tensile experiment, the yarn structure presents a sinusoidal curly form, and there are large gaps between the warp and weft yarns. Only through the contact friction force on the side can a sufficient number of interlaced knitting units be formed to generate friction force to make the whole fiber cloth tightly formed. As the drawing displacement gradually increases, the curly structure of the yarn is gradually straightened from the top to the bottom, and the knitting units are more closely formed into an interlocking structure between the warp and weft yarns to resist the drawing action. STF contributes less at this stage. When the warp and weft yarns are in full contact, the shear thickening fluid produces corresponding shear thickening or shear thinning behavior under the action of shear force, changing the magnitude of the friction force between the yarns. At this stage, the yarns are not pulled out and are still in the static friction stage. As the drawing displacement reaches the critical value, at this time the drawing force reaches the peak value, and the warp yarns begin to slide in and out of the intersection points of the knitting structure of the weft yarns, and the friction force between the yarns is converted into dynamic friction force. The drawing force-displacement curves of the four groups of yarn pulling experiments are as Figure 11 shown in (c1)-(c3) of (c) therein. In the static friction stage, the drawing force gradually increases with the increase of the displacement. The yarn mainly shows elastic deformation. The trend of the curve in the static friction stage is similar to the elastic stage of the force-deformation curve in the quasi-static tensile mechanical experiment of a single yarn. Because the yarn itself produces a certain amount of elastic deformation, although there is a relative displacement between the five yarns, they are still not pulled out, and the knitting structure of the composite fiber cloth has not been damaged. After removing the external force, the elastic deformation of the yarn can be restored, and the composite material can also be restored to the state before being stressed. When exceeding the peak point of the drawing force, the yarns are gradually pulled out and enter the dynamic friction stage. The "slip-stick" phenomenon appears in the drawing force-displacement curve, that is, the drawing force shows a periodic oscillation trend with the increase of the displacement, but the overall curve still shows an upward trend. The periodic oscillation is mainly because the pulling out of the warp yarns is from the intersection points of the weft yarns. The drawing force will destroy the tight interlocking structure between the warp and weft yarns in the previous stage, making the friction force generated after the yarns are misaligned decrease until the warp yarns continue to be pulled out to form the next interlocking structure, causing the drawing force to continue to rise, repeating this process to show a periodic oscillation trend. The curve shows an overall upward trend and is not affected by the reduction of the intersection points of the warp and weft yarns. This is because as the warp yarns are pulled out, although the contact area between the warp and weft yarns will decrease, the shear rate between the yarns will increase, and the viscosity of MSTF will increase with the increase of the shear rate, and the friction force between the yarns will increase instead. Macroscopically, the drawing force still shows an overall upward trend.
[0092] Comparison Figure 11In (c1), (c2), and (c3), the effects of modified additives on the pull-out behavior of MSTF-Kevlar composites were evaluated. It can be seen that the 57wt% SiO2 + 3wt% CNC-impregnated Kevlar fiber cloth and 57wt% SiO2 + 3wt% SiC maintained relatively stable frictional forces during the dynamic friction stage, and the amplitude of periodic oscillation was less than that of the 60wt% SiO2-impregnated fiber cloth. This indicates that the addition of modified additives helps to maintain the stability of the frictional force during yarn pull-out and avoids large fluctuations.
[0093] Appendix Figure 12 The experimental pictures of the yarn pull-out of four groups of MSTF (STF)-Kevlar composite yarns are shown. It can be seen that the yarn pull-out of the pure Kevlar fiber cloth shows a smaller yarn pull-out influence area (the area with obvious tensile displacement except for the five tensile yarns). This indicates that when the pure Kevlar fiber cloth yarn is stretched, the five tensile yarns independently resist the pull-out action and have little influence on the surrounding yarns. After impregnating with MSTF, the yarn pull-out influence area increases significantly, indicating that the increase in MSTF transfers the pull-out action borne by the five yarns to the surrounding yarns, enabling more yarns to participate in resisting the pull-out action.
[0094] Example 6:
[0095] In this study, a drop hammer testing machine (CEAST 935, energy range 0.59 - 757 J, impact speed 0.77 - 4.65 m / s) was used to conduct drop hammer impact tests on single-layer MSTF-Kevlar fiber cloth to characterize the mechanical response characteristics of MSTF-Kevlar composites under high strain rate impacts. By simulating the structural changes and energy absorption characteristics of MSTF-Kevlar composites when applied to the impact protection field through drop hammer impacts, the experimental characteristics of medium strain rate drop hammer impacts can ensure that MSTF exhibits good shear thickening characteristics when impacted, thereby enhancing the impact resistance of Kevlar fiber cloth, such as Figure 1As shown in (e). Three types of MSTF(STF)-Kevlar composites (Kevlar fiber cloth impregnated with 60wt% SiO2, Kevlar fiber cloth impregnated with 57wt% SiO2 + 3wt% CNC, Kevlar fiber cloth impregnated with 57wt% SiO2 + 3wt% SiC) were used in the experiment. At the same time, pure Kevlar fiber cloth was set as the control group. The size of each sample was a rectangle of 300×300mm. The diameter of the punch of the drop hammer testing machine was 16mm, the mass was 0.63kg, the head was hemispherical, and the drop hammer counterweight was 5Kg. The initial height of the drop hammer punch was controlled so that the impact energy carried when the drop hammer contacted the sample was 100J, and the impact point was the center of the rectangular sample. The rectangular single-layer MSTF(STF)-Kevlar fiber cloth was subjected to a circular fixed constraint by a circular clamp and a radial pre-tension was provided during clamping. After ensuring that the surface of the fiber cloth was tensioned and flat, it was placed at the lower support of the testing machine. The ambient temperature during impact was room temperature. During the impact process, the instrument synchronously recorded the change of force with displacement and the change of energy absorbed by the sample. Each sample was tested three times repetitively.
[0096] The force-displacement curves of the fiber cloth for the three experiments are shown respectively in Figure 13 (a), (b), and (c) in the appendix. From the appendix Figure 13It can be seen that the overall trends of the force-displacement curves of the four groups of materials are basically the same and can be divided into three stages. The first stage is the elastic stage, where the force increases linearly with displacement. Corresponding to when the drop hammer impact head contacts the fiber cloth specimen, the yarns of the fiber cloth undergo elastic tensile deformation, and the overall woven structure becomes tighter due to the impact load at the center, and the resistance of the yarns to the impact head, i.e., the total force on the yarns, gradually increases. The second stage is the falling stage. In this stage, under the action of the punch, most of the yarns in the impact contact area of the composite fiber cloth are squeezed to both sides of the impact head, resulting in lateral displacement and torsion. The woven structure of the fiber fabric is damaged by the punch, leading to a sudden decrease in the resistance of the composite fiber cloth to the impact head. However, there are still some yarns that still bear the impact load directly below the impact head and start to be pulled out under its action. Therefore, the force rises rapidly to the level before the decrease after the sudden decrease. The third stage is the oscillation stage. In this stage, the yarns gradually slip, and the form of friction between the yarns changes to be dominated by dynamic friction. The presented periodic oscillation trend corresponds to the oscillation phenomenon that appears in the yarn pull-out experiment. Since the MSTF is already under a relatively high strain rate condition, as the slip amount of the yarns gradually increases, the contact area and friction force between the warp and weft yarns decrease. Therefore, the force shows an overall downward trend during the oscillation. In the elastic stage, it can be seen that the force of the pure Kevlar fiber cloth increases gently with the increase of displacement, while the force of the fiber cloth impregnated with MSTF shows a significant upward trend. At the same time, the ultimate load of the MSTF(STF)-Kevlar composite material in the elastic stage is also significantly greater than that of the pure Kevlar fiber cloth. This proves that the addition of MSTF(STF) can significantly improve the stiffness and ultimate impact resistance of the Kevlar fiber cloth in the elastic stage under impact load conditions at a relatively high strain rate. Calculate the curve integrals of the three stages for the force-displacement curves of the four groups of MSTF(STF)-Kevlar composite material fiber cloths. The absolute area integral value can measure the amount of energy absorbed during the impact process of the composite material. It can be seen that the most energy is absorbed in the fluctuation stage (accounting for about 50%), followed by more energy absorption in the elastic stage (accounting for about 30%). Compared with the pure Kevlar fiber cloth, the introduction of MSTF can significantly increase the energy absorption values in the elastic stage and the oscillation stage, making the impact energy absorption effect of the MSTF-Kevlar composite material significant. Considering that the woven structure of the fiber cloth has been damaged and become loose when entering the falling stage, if it bears a secondary impact, there is no complete structure to produce elastic deformation, and the displacement of the yarns of the fiber cloth in the third stage has exceeded the protection requirements. Therefore, define the peak force at the end of the first stage as the critical force at which the composite fiber cloth loses its protection effect under impact, and use it as an important index to evaluate the protection performance of the composite fiber cloth. Statistically analyze the peak forces of each experimental curve and calculate the average value, variance, and standard deviation. The results are shown in Table 3 below.
[0097] Table 3 Peak Forces of the Curves in the Drop Hammer Impact Experiment
[0098]
[0099] As can be seen from Table 3, the average peak force of the 57 wt% SiO2 + 3 wt% CNC-impregnated Kevlar fiber cloth is the largest (10 times higher than that of the pure Kevlar fiber cloth). The average peak force of the 60 wt% SiO2-impregnated Kevlar fiber cloth is slightly lower than that of the composite material with CNC added. The average peak force of the 57 wt% SiO2 + 3 wt% SiC-impregnated Kevlar fiber cloth is significantly less than the former two, indicating that the MSTF-Kevlar composite material with CNC additive has the best protective performance. By analyzing the variance and standard deviation to conduct a discrete analysis of the four groups of materials, it can be seen that the variance and standard deviation of the 57 wt% SiO2 + 3 wt% SiC-impregnated Kevlar fiber cloth are the lowest among the three groups of MSTF-Kevlar composite materials with different ratios, which indicates that the addition of SiC can significantly enhance the stability of the impact resistance performance of the composite material.
[0100] The drop hammer impact experiment also needs to evaluate the anti-impact protection performance of the MSTF-Kevlar composite material from the perspective of energy. During the impact process of the composite material fiber cloth, the speed of the drop hammer starts to decrease after contacting the fiber cloth. According to the principle of energy conservation, this part of kinetic energy will be absorbed by the composite fiber cloth. Therefore, considering the protection ability of the protective equipment from the perspective of the maximum energy that the human body can bear, the absorption value of the impact energy by the protective material is used as an important index to judge the performance of the protective material. The absorption energy-displacement curve of the repeated drop hammer impact experiment of the MSTF-impregnated Kevlar fiber cloth and the pure Kevlar fiber cloth is as attached Figures 14 - 16 shown. As can be seen from the attachment Figures 14 - 16 , for the impact energy absorption curve of the pure Kevlar fiber cloth, it can be generally divided into three stages. In the first stage, the displacement increases rapidly and the energy absorption is slow. In the second stage, the displacement continues to increase and the energy absorption rises until the highest point. In the third stage, after passing the highest point of energy, the displacement increases slightly and the energy rapidly decreases to zero. At this time, the fiber cloth is penetrated, the fiber filaments break, and the energy absorption rapidly decreases. The overall trends of the three ratios of MSTF (STF)-Kevlar composite materials are similar and can be generally divided into three sections, namely StageⅠ, StageⅡ, and the middle platform stage. The appearance of the platform stage may be due to the lateral displacement and torsion of the yarns near the punch, which also corresponds to the descending stage in the attachment Figure 13 . The overall energy absorption shows an upward trend, but compared with StageⅠ, the upward trend in StageⅡ slows down (attachment Figures 14 - 16The pie chart shows the slopes of the two stages of each curve. In the second and third repeated experiments of the 60wt% SiO2-impregnated Kevlar fiber cloth and the 57wt% SiO2 + 3wt% SiC-impregnated Kevlar fiber cloth, the Stage II curve even remained flat, indicating that the energy absorption efficiency in Stage II had decreased significantly. Only the 57wt% SiO2 + 3wt% CNC material maintained a relatively high upward trend in the Stage II curve in all three experimental curves, with a relatively high energy absorption efficiency and the highest energy absorption value at the end of the second stage. This indicates that the CNC additive effectively improved the energy absorption efficiency and the total energy absorption value. However, considering the overall energy absorption curve, the energy absorption capacity of the three types of Kevlar fiber cloths with MSTF addition was significantly improved. Considering that excessive deformation of the fiber cloth would lead to a weakened or even lost protective ability, the energy at a displacement value of 80 mm was taken as the maximum absorbed energy. The energy absorption rate and the average energy absorption value in Stage I of the three experiments are shown in Table 4 below.
[0101] Table 4 Energy absorption rate and average energy absorption value in Stage I of the three experiments
[0102]
[0103] As can be seen from Table 4, the 57wt% SiO2 + 3wt% CNC had the highest maximum absorbed energy value (average value of 51.3) and the highest energy absorption rate in Stage I (1.22 J / mm). The maximum energy absorption value and the energy absorption efficiency of the composite material with both SiC and 60% SiO2 added were significantly improved compared to the pure Kevlar fiber cloth. This indicates that MSTF has a significant effect on enhancing the energy absorption performance of the fiber cloth, and the modification with the CNC additive results in the strongest energy absorption effect.
[0104] The above shows and describes the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. What is described in the above embodiments and the specification only illustrates the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention will have various changes and improvements, and these changes and improvements fall within the scope of the present invention claimed. The scope of protection claimed by the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation method of a multiphase shear thickening fluid-Kevlar fiber composite material, characterized in that, It includes the following steps: S1: Add a modified additive to the shear thickening fluid to prepare a multiphase shear thickening fluid; S2: Impregnate Kevlar fibers with the multiphase shear thickening fluid prepared in step S1 to obtain a multiphase shear thickening fluid-Kevlar fiber composite material.
2. The preparation method of a multiphase shear thickening fluid-Kevlar fiber composite material according to claim 1, characterized in that, The modified additive described in step S1 includes CNC or SiC.
3. The preparation method of a multiphase shear thickening fluid-Kevlar fiber composite material according to claim 2, characterized in that, The specific operation of step S1 includes the following steps: S101: Gradually add nano-SiO2 to the dispersion medium PEG200 and stir until it becomes a uniform suspension to obtain a shear thickening fluid without a reinforcing phase; S102: Gradually add the modified additive CNC or SiC to the shear thickening fluid and stir evenly to obtain a multiphase shear thickening fluid sample containing a reinforcing phase; S103: Cure the multiphase shear thickening fluid sample at a constant temperature and humidity for 12 hours to remove the bubbles in the sample and obtain the finished multiphase shear thickening fluid.
4. The preparation method of a multiphase shear thickening fluid-Kevlar fiber composite material according to claim 3, characterized in that, The mass ratio of nano-SiO2 to PEG200 is 5-7:3-5; the mass ratio of nano-SiO2 to the modified additive is 5-7:1-3.
5. The preparation method of a multiphase shear thickening fluid-Kevlar fiber composite material according to claim 3, characterized in that, The conditions for curing at a constant temperature and humidity in step S103 are: 30°C, 95% humidity.
6. The preparation method of a multiphase shear thickening fluid-Kevlar fiber composite material according to claim 1, characterized in that, The specific operation of step S2 includes the following steps S201: Dilute the multiphase shear thickening fluid prepared in step S1 with absolute ethanol and ultrasonically disperse and mix evenly; S202: Immerse the Kevlar fiber cloth in the mixture in step S201, stir, take it out and dry it to obtain a multiphase shear thickening fluid-Kevlar fiber composite material.
7. The preparation method of a multiphase shear thickening fluid-Kevlar fiber composite material according to claim 1, characterized in that, In step S202, the impregnation time of the Kevlar fiber cloth is 5 min, the drying temperature is 40°C, and the drying time is 6 h.
8. A multiphase shear thickening fluid-Kevlar fiber composite material prepared by the preparation method described in any one of claims 1-7.
9. The application of the multiphase shear thickening fluid-Kevlar fiber composite material as described in claim 8 in an impact-resistant protective material.
10. The performance testing method of the multiphase shear thickening fluid-Kevlar fiber composite material according to claim 8, characterized in that, It includes the following steps Step a: Conduct an electron microscopy experiment on the multiphase shear thickening fluid-Kevlar fiber composite material; Step b: Conduct room temperature rheological experiments and variable temperature rheological experiments on the multiphase shear thickening fluid; Step c: Conduct a single yarn quasi-static tensile mechanical test on the multiphase shear thickening fluid-Kevlar fiber composite material; Step d: Conduct a pull-out test on the multiphase shear thickening fluid-Kevlar fiber composite material under an impact load; Step e: Conduct a drop hammer impact test on the multiphase shear thickening fluid-Kevlar fiber composite material.
Citation Information
Patent Citations
Ultra-precise curved surface finishing method based on non-Newtonian fluid shear thickening effect
CN102717325A
Shear thickening liquid / bacterial cellulose-silica composite material and preparation method thereof
CN110760102A
Shear thickening protective liquid and application thereof
CN111910436A
Shear thickening fluid as well as preparation method and application thereof
CN115595120A
Shear thickening formulation and composite material employing the same
US20160059195A1